Determinants Influencing the Customer Attitude in Online Shopping in Hanoi - Luc Manh Hien; Le Thi Hai Ha (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
This research was undertaken to determine the factors affecting customer attitude in online shopping in Hanoi. The author conducted a survey and collected 245 valid responses. This research employed quantitative analysis techniques such as Cronbach Alpha analysis, and regression analysis. The research results showed that two factors were identified (in descending order of importance), including perceived usefulness, and compatibility. The results of this study provide internet business managers with insights and tools that they can use to build and improve consumer attitudes. Some recommendations are made to improve the competitive advantage in online sales firms.